2021
DOI: 10.34293/education.v9i4.4027
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning Readiness, Phubbing and Sofalizing Levels of Pre-Service Teachers amidst Pandemic

Abstract: With the effect of the pandemic, online learning has gained importance. In addition, due to restrictions, individuals’ behavior with digital tools has begun to change. Thus, the present study examines online learning readiness, phubbing, and sofalizing behavior in pre-service teachers and the correlations between these variables in a completely online instruction environment. A correlational design was adopted in the study. The study was carried out with 130 pre-service teachers. The data were collected with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
2
1
1
Order By: Relevance
“…The study findings showed that the overall OLR of pre-service teachers improved. This finding was consistent with the literature (Chung et al, 2020;Hung et al, 2010;İlic, 2021b;Yurdugül & Demir, 2017). It could be suggested that ICT skills improved due to the required online learning environment and the Information Technologies Course.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study findings showed that the overall OLR of pre-service teachers improved. This finding was consistent with the literature (Chung et al, 2020;Hung et al, 2010;İlic, 2021b;Yurdugül & Demir, 2017). It could be suggested that ICT skills improved due to the required online learning environment and the Information Technologies Course.…”
Section: Discussionsupporting
confidence: 93%
“…In the study, it was determined that OLR did not differ based on gender. This finding was in line with the findings reported in several studies (Atkinson & Blankenship, 2009;Chung et al, 2020;İlic, 2021b;Masters & Oberpriles, 2004). At the beginning of the term, the OLR of males was better; however, OLR scores of the females were higher at the end of the semester.…”
Section: Discussionsupporting
confidence: 93%
“…The findings demonstrated that the OLR levels of the participants did not change with the adoption of blended education. This finding was inconsistent with the findings in the literature (Chung, Subramaniam, & Dass, 2020;Martin, Stamper, & Flowers, 2020;Çiğdem & Özkan, 2022;İlic, 2021b;Magogwe et al, Studies investigating the online satisfaction levels of the participants could be conducted in addition to OLR.…”
Section: Discussioncontrasting
confidence: 69%
“…There was no study that examined the variables in the process, which was carried out entirely with distance education during the pandemic and then as a blended. These conditions and the need for studies investigating OLR levels (Ates-Cobanoglu & Cobanoglu, 2021;Yu, 2018), especially the need for longitudinal studies (İlic, 2021b;Tang et al, 2021), show the lack of literature. Thus, the current study aimed to examine the OLR situations of the learners in purely distance and blended learning environments where the flipped classroom is used.…”
Section: Literature and Aim Of The Studymentioning
confidence: 99%